Organoleptic rating of RTS prepared from pulp of Bael cultivars (Indian Journal of Arid Horticulture, 2013)
Bael (Aegle marmelos Correa.) is a nutritive and medicinally important fruit and also known as bilvpatra, beel,  shriphal and Bengal quince. Fruit is eaten as fresh and also used for making several value added products. All the parts of the  bael tree viz. stem, bark, root, leaf, flowers, seed oil or fruits of any stage of maturity and ripen are used for preparation of  Ayurvedic medicines and it is major constituent of Dashmool. The fruit is generally available from March to May month.  Important aspect of fruit is therapeutic and neutraceutical value, which could safeguard stomach ailments and improve  health of rural populations. The bael pulp is used as a base of various products like squash, jam, toffee, slab, powder, nectar,  beverage, RTS, etc. Bael fruit pulp of cultivar NB-5, CISH Bael-2 and Goma Yashi was used to make ready to serve drink by  adding sugar @ 700g/l of pulp or juice. This RTS was further diluted with water in 30:70 for sensory evaluation to assess the  quality of products. Organoleptic score indicated that ready to serve drink varied among pulp of bael varieties and RTS  prepared from pulp of Goma Yashi was found better by getting highest score than other varieties. The utilization of bael  fruits pulp for preparation of delicious drink has been discussed in this paper.
Keywords: Bael; Aegle marmelos; RTS; fruit pulp; value addition